Simultaneous ultrasonography and arthroscopy for the study of the joint environment: indications and limits - E. Valcamonica; E. Schito; L. Pisoni; O. Epis; A. Murgo; E. Paresce; O. De Lucia; C. Piana; F. Fantini (PAGEPress Publications, 2011)
Arthroscopy is a mini-invasive technique that allows the direct observation of the joint cavity and the execution of diagnostic and therapeutic procedures; arthroscopy needs a very long learning-time curve as well as dedicated spaces and instruments. Ultrasonography is an imaging technique that enables to perform an immediate extension of the standard physical examination. The opportunity to visualize soft tissues, to obtain multiplanar and dynamic images in real time makes this practice easy repeatable at low costs. Ultrasonography allows to detect a variety of changes during inflammatory processes. The wide experience in arthroscopy of rheumatic patients acquired through the years by our team at the G. Pini Institute led us to study in vivo, during arthroscopy, the correspondence between arthroscopic and ultrasonographic images. Up to now three knee arthroscopies have been conducted with the double equipment (ultrasonographic and arthroscopic devices) in operating room. In our experience, the combination of the two methods in operating room may improve the validation of ultrasonography with arthroscopy as gold standard, helps to train the ultrasonographer to give immediate answers in order to clear the doubts aroused by ultrasonographic images; it also allows the arthroscopist to visualize the deeper layers of the synovial membrane making double guided targeted biopsies possible. Limits are the complexity of the procedure (instruments, operators, spaces, training of the doctors), the loose of power-doppler signal with the blood tourniquet and the always difficult evaluation of cartilage.